2013
DOI: 10.1186/1471-230x-13-85
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of irsogladine or omeprazole on non-steroidal anti-inflammatory drug-induced esophagitis, peptic ulcers, and small intestinal lesions in humans, a prospective randomized controlled study

Abstract: BackgroundProton-pump inhibitors such as omeprazole are a standard treatment to prevent non-steroidal anti-inflammatory drug-induced upper gastrointestinal mucosal injuries. However, it is unclear which drugs may protect against all NSAID-induced digestive-tract injuries. Here, we compare the efficacy of the gastromucoprotective drug irsogladine with omeprazole in preventing NSAID-induced esophagitis, peptic ulcers, and small-intestinal mucosal injury in healthy subjects.MethodsThirty-two healthy volunteers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…PPIs reduce the occurrence of peptic ulcers and are an important treatment for acute non-variceal upper gastrointestinal bleeding [21]. By contrast, acid inhibition does not confer protection to NSAID-induced damage distal to the ligament of Treitz [16,[22][23][24], and, in fact, studies report that PPIs could contribute to small intestinal injury. Wallace et al [13] and Blacker et al [25] have reported that PPIs exacerbate NSAID-induced small intestinal injury in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…PPIs reduce the occurrence of peptic ulcers and are an important treatment for acute non-variceal upper gastrointestinal bleeding [21]. By contrast, acid inhibition does not confer protection to NSAID-induced damage distal to the ligament of Treitz [16,[22][23][24], and, in fact, studies report that PPIs could contribute to small intestinal injury. Wallace et al [13] and Blacker et al [25] have reported that PPIs exacerbate NSAID-induced small intestinal injury in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these promising developments, in the present study, we found that both IRS and REB as well as MIS could prevent the intestinal lesions caused by DIC with or without antisecretory drugs. Furthermore, several recent pilot studies using CE have revealed that both IRS (Kuramoto et al, 2013) and REB (Niwa et al, 2008;Mizukami et al, 2012), as well as MIS (Watanabe et al, 2008;Fujimori et al, 2009) are effective in limiting the small intestinal side effects of aspirin and other NSAIDs, including DIC. Taking all the present findings and the clinical findings in healthy volunteers together, it is concluded that both IRS and REB could be used as new candidate drugs for the treatment of intestinal lesions induced by NSAIDs with and without antisecretory drugs.…”
Section: Prevention Of Intestinal Ulcer By Mucosal Protective Drugsmentioning
confidence: 99%
“…In recent studies, several drugs such as misoprostol [4], rebamipide [21-23], irsogladine [24], and probiotic Lactobacillus casei [25] have been reported to be effective for the treatment of NSAID-induced enteropathy, including enteropathy induced by LDA. However, these studies were limited by the characteristics of the subjects enrolled.…”
Section: Discussionmentioning
confidence: 99%